Designing Innovative Learning Models for History Learning - Wibowo, Bayu Ananto; Sutimin, Leo Agung (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
This research discusses the importance of innovative learning models in the context of history learning. This research uses the literature study method. The purpose of this research is to explore the importance of innovative learning models, particularly project-based learning models, in the context of history learning. The results of this study illustrate how project-based learning models with a student-centred learning approach, learning strategies that include planning, method implementation, and evaluation, as well as learning methods and techniques such as assignments, group work, discussions, and presentations, are described as ways to enable students to actively engage in learning and develop social, collaborative, and problem-solving skills. In addition, innovative learning models such as E-Learning with PAIKEM approach and Contextual Teaching and Learning with PASA model are also mentioned as methods that can help students understand history multidimensionally, improve critical thinking skills, and prepare them to be informed global citizens.